Effects of dietary oat proteins on cholesterol metabolism of hypercholesterolaemic hamsters. (21st May 2015) - Tong, Li‐Tao; Guo, Lina; Zhou, Xianrong; Qiu, Ju; Liu, Liya; Zhong, Kui; Zhou, Sumei
Abstract: BACKGROUND: The aim of present study was to investigate the hypocholesterolaemic effects of oat proteins (OP) in hamsters fed with a hypercholesterolaemic diet. The hamsters were divided into five groups and fed with the experimental diets containing oat, OP, oat β ‐glucan (OG), or OP+OG for 30 days. RESULTS: OP and the OG significantly lowered the concentrations of plasma low‐density lipoprotein‐cholesterol and liver total cholesterol (TC), and increased the excretion of faecal bile acid and TC. Plasma and liver TC in the OP+OG group were significantly lower than those in the OP or OG groups. Both OP and OG increased the activity of liver cholesterol 7 α ‐hydroxylase (CYP7A1), while its activity in the OP+OG group was strongly increased compared with the OP or OG groups. CONCLUSION: These results indicated that dietary OP could improve hypercholesterolaemia, while dietary OP and OG together would have better hypocholesterolaemic effects. © 2015 Society of Chemical Industry